2014
DOI: 10.7314/apjcp.2014.15.16.6805
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Tunisia: Association of Body Mass Index with Histopathological Aspects of Tumors

Abstract: Background: Previous studies have suggested a link between obesity and breast cancer (BC). However, there is no universal consensus, especially in population based studies. Because only few studies have been conducted on African women, we aimed here to assess the relationship between BMI at time of diagnosis and the BC histopathological features among Tunisian patients according to menopausal status using a hospital-based prospective cohort study. Materials and Methods: Clinical and pathological data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The 20-year study of breast cancer in Tehran demonstrated a significant difference for the mean age (47.2, 48.8, 49.2 years) at time intervals respectively (1985-1995, 1996-2000 and 2001-2006) (Harirchi et al, 2010). In another study performed on five different provinces of Iran in 2000, the mean age at diagnosis was 46±12 years (Vostakolaei et al, 2012) and in the study of Hichem Bouguerra mean age of cases was 50.9±11.9 (Bouguerra et al, 2014). Breast cancer median age at the diagnosis was 46 years in 2004-2009 in ethnic disparity Iran study (Harirchi et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…The 20-year study of breast cancer in Tehran demonstrated a significant difference for the mean age (47.2, 48.8, 49.2 years) at time intervals respectively (1985-1995, 1996-2000 and 2001-2006) (Harirchi et al, 2010). In another study performed on five different provinces of Iran in 2000, the mean age at diagnosis was 46±12 years (Vostakolaei et al, 2012) and in the study of Hichem Bouguerra mean age of cases was 50.9±11.9 (Bouguerra et al, 2014). Breast cancer median age at the diagnosis was 46 years in 2004-2009 in ethnic disparity Iran study (Harirchi et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Basal-type cancers are seen in only 15% of this population [6]. On the other hand, triple-negative cancers are seen with greater frequency among blacks, accounting for as high as 60.5% of all breast cancer cases in some African studies [4,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In our study, most cancers (41.9%) were of high nuclear grade, triple negative (42.1%), and unassociated with DCIS (52.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the FTO gene is located on chromosome 16, and has a close link with BMI. On the other hand, Bouguerra et al [152] noticed that obesity was correlated with larger tumors, advanced grade and with ER−, progesterone receptor negative (PR−), and HER2+ breast cancer subtype. Similarly, in a study conducted by Mazzarella et al [153], obesity significantly correlated with worse overall survival and cumulative incidence of distant metastases in ER−/HER2+ breast cancer.…”
Section: Clinical Studies On Breast Cancer and Her2 With Reference Tomentioning
confidence: 99%